COMMUNITY PARTICIPATION AND SOCIAL RECONSTRUCTION POST NATURAL DISASTERS BASED ON LOCAL WISDOM IN SIGI DISTRICT CENTRAL SULAWESI PROVINCE - Muhamad, Hasan; Abdulah, Dewi Cahyawati; Ariani, Nora; Afdal, Afdal (LPPM Universitas Jambi, 2025)
This study investigates two key objectives: (1) the role of community participation and social reconstruction following the earthquake and liquefaction disaster in Sigi Regency and (2) the strategic utilization of local wisdom as a foundational element for long-term recovery and resilience. Employing a qualitative research design, the study collected both primary and secondary data through observations, in-depth interviews, Focus Group Discussions (FGDs), and documentation, supported by the Participatory Rural Appraisal (PRA) approach to ensure community engagement and contextual depth. Findings reveal that post-disaster community participation was notably high, with active involvement in reconstruction efforts, leading to widespread support for rehabilitation programs initiated by both governmental and traditional institutions. Furthermore, the revival and application of the molibu tradition, a local wisdom-based reconciliation and decision-making practice, emerged as a powerful cultural mechanism that significantly enhanced social reconstruction. The study found that, before incorporating this tradition, there was limited participation from key community actors, particularly traditional leaders. This research presents a culturally grounded model of disaster recovery, emphasizing the integration of Indigenous knowledge systems, such as Molibu, into formal post-disaster management strategies. It contributes to both academic discourse and practical policy by producing a Sinta-indexed journal article, a localized disaster management textbook, and recommendations for regional policymaking. The study also advocates for the institutionalization of local wisdom at the village level, ensuring its transmission across generations and its sustainability as a tool for resilience in disaster-prone communities.